Fonologi Bahasa Arab Anak Usia 2 s.d. 8 Tahun dalam Membaca Al-Qur’an Metode Ummi PPAS Hidayatullah Ponorogo - Amrullah, Sulton Azali; Pratama, Toni Diyan; Wijayanti, Lisma Meilia; Muqorrobin, Syamsul; Salma, Kunti Nadiyah (Institut Agama Islam Sunan Giri Ponorogo, 2022)
Research related to the acquisition of Arabic in reading the Qur'an in children is exciting to study because by doing this research, researchers can find out the mistakes of children in obtaining Arabic when reading the Qur'an. This research was conducted on several students at PPAS Hidayatullah Ponorogo. Data collection techniques were carried out using recording, listening, and note-taking techniques. The researcher also conducted interviews related to the life of the informant and one of the clerics. This study indicates that the makhorijul letters spoken by the informants are still not perfect in pronunciation. Generally, the error is in the form of inaccurate makhorijul letters in the informant's reading.